WORKING IN RETIREMENT: OPPORTUNITIES, BARRIERS & RISKS - Dr. , Dimpy Mahanta (International Journal of Psychosocial Rehabilitation, 2011)
Increasing longevity is one of the biggest achievements of the last century. The demographic changes brought about by increased life expectancy are one of the biggest challenges society is facing now. There are increasingly less active citizens to pay for the retired and aging population. This called for the retired and aged to be more actively involved on the professional front. Working during retirement used to be considered as an oxymoron. Yet, as growing numbers of workers continue to work for pay during their so-called “retirement”, this is no longer the case. Therefore, an understanding of ‘working in retirement’ is particularly important in light of today’s aging society. The presented paper discusses this theme taking into consideration a number of intervening factors such as, the reasons for people deciding to work after retirement, as well as the reasons for retiring in the first place; various types of works available to the older employees; and barriers to working in retirement. The paper also discusses the retirement risks in terms of financial security, with a special emphasis on retiring women. Apart from this, the implications of the emerging trend of working in retirement for older employees as well as the employers are also presented.